2015
DOI: 10.1093/molehr/gav037
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the HLA-G promoter is associated with preeclampsia

Abstract: Preeclampsia (PE) is a severe pregnancy-induced disorder characterized by hypertension and proteinuria and a leading cause of perinatal maternal-fetal mortality and morbidity in developing countries. Dysregulated human leukocyte antigen (HLA)-G was found in placentas as well as in maternal sera from PE patients; however, the reason for this difference is unknown. As accumulating evidence has confirmed that DNA methylation is an important mechanism for regulating gene expression, we sought to test the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 35 publications
2
31
0
1
Order By: Relevance
“…According to the results of a PCR array analysis of epigenetic modification enzymes, the expression of DNMT1 was altered to the greatest extent in the BPA-induced preeclampsia-like mouse model, whereas the levels of DNMT3a and -3b and TET1, -2, and -3 were not affected. This finding indicates a role for DNMT1-mediated methylation reprogramming, which is manifested in the placentas of women with preeclampsia (37). Using HTR8/ SVneo cells, we confirmed that BPA exposure downregulates WNT signaling by increasing DNA methylation in the promoter region of the WNT2 gene through DNMT1.…”
Section: Discussionsupporting
confidence: 64%
“…According to the results of a PCR array analysis of epigenetic modification enzymes, the expression of DNMT1 was altered to the greatest extent in the BPA-induced preeclampsia-like mouse model, whereas the levels of DNMT3a and -3b and TET1, -2, and -3 were not affected. This finding indicates a role for DNMT1-mediated methylation reprogramming, which is manifested in the placentas of women with preeclampsia (37). Using HTR8/ SVneo cells, we confirmed that BPA exposure downregulates WNT signaling by increasing DNA methylation in the promoter region of the WNT2 gene through DNMT1.…”
Section: Discussionsupporting
confidence: 64%
“…The pathophysiological mechanism behind would be a reduced expression of HLA‐G associated with certain HLA‐G gene polymorphisms and haplotypes as described above. Such an aberrant or reduced expression of HLA‐G has also been observed in preeclampsia in many other studies , which in theory would result in disturbances in the immunological fetomaternal crosstalk. The results of the current large and comprehensive study do not indicate that specific basic fetal HLA‐G gene sequence variation with relevance for the HLA‐G protein expression by the trophoblast cells in the placenta explain the low expression of HLA‐G in cases of severe preeclampsia.…”
Section: Discussionsupporting
confidence: 57%
“…One study found that the HLA-G promoter region was significantly more methylated in cases of preeclampsia compared with controls. This was associated with reduced HLA-G expression (63). Another of our own recent studies reported the phenomenon of allelic imbalance in HLA-G 14-bp ins/del heterozygous first trimester trophoblast cells (58).…”
Section: Discussionmentioning
confidence: 84%
“…40 Increased DNMT1 and DNMT3B correlate with decreased expression of syncytin-1, GATAD1, and HLA-G in preeclamptic placentas, which are key factors in trophoblast. [41][42][43] These findings stimulate interest in investigating the roles of DNMT1 and DNMT3B in PE in future studies.…”
Section: Discussionmentioning
confidence: 88%